2021
DOI: 10.3389/fpls.2021.757925
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles: Emerging Players in Plant Defense Against Pathogens

Abstract: Communication between plants and interacting microorganisms requires functional molecule trafficking, which is essential for host defense and pathogen virulence. Extracellular vesicles (EVs) are single membrane-bound spheres that carry complex cargos, including lipids, proteins, and nucleic acids. They mediate cell-to-cell communication via the transfer of molecules between cells. Plant EVs have been isolated from many plant species and play a prominent role in immune system modulation and plant defense respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 90 publications
(171 reference statements)
1
24
0
1
Order By: Relevance
“…Suresh et al reported a higher yield of PELNs when PEG precipitation was carried out in pH 4 and 5 (58). PELNs can be internalized in plant cells, mammalian cells, fungi, and bacteria (28,(45)(46)(47). Created with BioRender.com.…”
Section: Pelns Biogenesis and Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Suresh et al reported a higher yield of PELNs when PEG precipitation was carried out in pH 4 and 5 (58). PELNs can be internalized in plant cells, mammalian cells, fungi, and bacteria (28,(45)(46)(47). Created with BioRender.com.…”
Section: Pelns Biogenesis and Isolationmentioning
confidence: 99%
“…(C) Components: Generally, PELNs contain fewer proteins and miRNAs than exosomes. (D) Targets:PELNs can be internalized in plant cells, mammalian cells, fungi, and bacteria(28,(45)(46)(47). Created with BioRender.com.…”
mentioning
confidence: 99%
“…Additionally, plant-derived exosome-like nanoparticles (ELNs) have also been characterized, and broccoli-derived nanoparticles were determined, from size distribution, to be on average 32.4 nm in diameter [185]. Although plant exosomes contain small molecules and proteins toxic to pathogenic fungi [186], their precise biogenesis remains obscure [187,188] and the parts remain largely uncharacterized [176]. The situation for animal systems is much farther advanced, and in these a hypothetical pathway for vesicle biogenesis has been proposed [189].…”
Section: On the Origin Supramolecular Aggregation And Mode Of Action Of Humic Substancesmentioning
confidence: 99%
“…The natural traffic and delivery of these small RNA molecules inside and between interacting plant-pathogen organisms can be done through extracellular vesicles (EVs), i.e., membrane-bound particles that carry manly transmembrane proteins and RNAs, being produced by both sides of the pathosystem ( Liu et al, 2021 ). In plants, stress-associated EVs were isolated and characterized in apoplast fluids from Arabidopsis leaves, from where they are assimilated by the pathogen/pest ( Rutter and Innes, 2017 ).…”
Section: Rnai Plant-based Technologiesmentioning
confidence: 99%